Quality screening for air quality monitoring data in China. (September 2016) - Liu, Jianzheng; Li, Weifeng; Li, Jie
Abstract: Particulate matter data obtained from the national air quality monitoring network in China has become an essential and critical data source for many current and forthcoming studies as well as the formulation and implementation of air pollution regulatory policies on particulate matter (PM2.5 and PM10 ). However, the quality control of this data is dubitable and can affect many future studies and policies. This study identifies and elucidates two significant quality control issues with the data. They are PM2.5 levels exceeding concurrent co-located PM10 levels and the registration of same concentrations for consecutive hours at some stations. Future studies utilizing particulate matter data need to acknowledge and address these issues to ensure accurate and reliable results. Highlights: The study identifies two significant quality issues with China air monitoring data. PM2.5 measurements incorrectly exceed co-located PM10 levels measured concurrently. Same PM measurements are registered for consecutive hours at same stations. Researchers are advised to use particulate matter data with prudence and caution. Abstract : This study identifies and elucidates two significant quality control issues with the national air quality monitoring data in China which may affect many future studies and policies.